Building Europe’s identity through the societal constitutionalism: Do we need a new European constitutional governance? - Francesca Scamardella (European Law Open)
Jiří Přibáň’s work deals with constitutional imaginaries, starting from the concept of social imaginaries as entities describing functionally differentiated modern society as one polity. Přibáň’s conception perceives constitutional imaginaries in terms of social systems, representing a socio-legal paradox, since constitutional imaginaries express both the constitution of social unity and its pluralism of values. The aim of this contribution is to explore the link between Přibáň’s work and some aspects of Luhmann and Teubner’s contributions to the theory of social systems. By highlighting these features, the Author tries to argue that contemporary imaginaries can work as constitutional forces that drive contemporary legal pluralistic regimes, including the European one, to the societal unity by warranting a systemic difference.